PERAN TEKNOLOGI INFORMASI DALAM MEMBANGUN AGILITAS LEMBAGA PERPUSTAKAAN - Andi Asari (Jurnal Manajemen dan Ekonomi Kreatif, 2023)
The organization more and more invests in information technology (IT) to increase agility/agility. It is generally believed that organizations with larger IT investments tend to be more agile in responding to environmental changes. However, the problem of whether IT is a supporter or inhibiting organizational agility is still not resolved. Based on the theory of resource -based views and literature of information technology capabilities and organizational agility, the authors develop and test theoretical models that integrate IT capabilities, and agility of the institution. This article highlights the role of the process of developing the agility of library institutions supported by IT capabilities. We base our reviews on many literature taken from several international journals and conferences. We review the use of various theoretical lenses used to investigate the relationship between IT capabilities and the agility of the library organization. We also map literature through a series of stages that highlighted how researchers had built in previous studies. Finally, we discuss opportunities for future research in an effort to cover the gap of various research findings.